Oligothiophene-ring-strapped perylene bisimides: functionalizable coaxial donor-acceptor macrocycles - Dnyaneshwar Veer, Sairam; Chandrakant Wakchaure, Vivek; Asokan, Kiran; Dixit, Ruchi; Goswami, Tanmay; Saha, Ramchandra; Gonnade, Rajesh; Ghosh, Hirendra N.; Santhosh Babu, Sukumaran (Angewandte Chemie-International Edition, 2023)
Aesthetic designs from nature enable new knowledge to be gained and, at the same time, inspire scientific models. In this context, multicomponent macrocycles embody the advantage of precisely positioning the structural units to achieve efficient communication between them. However, the construction of a functionalizable macrocycle for ultrafast charge separation and stabilization has not been attempted. Herein, we report the synthesis, crystal structure, and transient absorption of a new functionalizable macrocycle consisting of an oligothiophene-ring-strapped perylene bisimide. Transient absorption results point to a sequential improvement in charge separation and stabilization from the macrocycle to the corresponding linear dimer and 2D polymer due to the unique design. Our macrocycle design with a supportive spatial arrangement of the donor and acceptor units will inspire the development of more complex synthetic systems with exciting electron-transfer and charge-separation features.
Keywords: Charge Separation; Donor-Acceptor Systems; Electron Transfer; Macrocycles; Perylene Bisimides

Boron- and oxygen-doped π-extended helical nanographene with circularly polarised thermally activated delayed fluorescence - Venugopal, Geethu; Kumar, Viksit; Jadhav, Ashok Badrinarayan; Dongre, Sangram D.; Khan, Abujunaid; Gonnade, Rajesh; Kumar, Jatish; Santhosh Babu, Sukumaran (Chemistry-A European Journal, 2024)
Helical nanographenes have garnered substantial attention owing to their finely adjustable optical and semiconducting properties. The strategic integration of both helicity and heteroatoms into the nanographene structure, facilitated by a boron-oxygen-based multiple resonance (MR) thermally activated delayed fluorescence (TADF), elevates its photophysical and chiroptical features. This signifies the introduction of an elegant category of helical nanographene that combines optical (TADF) and chiroptical (CPL) features. In this direction, we report the synthesis, optical, and chiroptical properties of boron, oxygen-doped pi-extended helical nanographene. The pi-extension induces distortion in the DOBNA-incorporated nanographene, endowing a pair of helicenes, (P)-B2NG, and (M)-B2NG exhibiting circularly polarized luminescence with glum of -2.3x10-3 and +2.5x10-3, respectively. B2NG exhibited MR-TADF with a lifetime below 5 mu s, and a reasonably high fluorescence quantum yield (50 %). Our molecular design enriches the optical and chiroptical properties of nanographenes and opens up new opportunities in multidisciplinary fields. B, O-doped pi-extended helical nanographene has been explored for its optical and chiroptical properties. The presence of helical and nanographene segments stabilize the helicity and imparts tunable optical properties. Helical nanographene display circularly polarized thermally activated delayed fluorescence. image
Keywords: circularly polarized luminescence; DOBNA; dual emission; nanographene; TADF

Oligo(phenyleneethynylene)s: shape-tunable building blocks for supramolecular self-assembly - Fernandez, Zulema; Sanchez, Luis; Santhosh Babu, Sukumaran; Fernandez, Gustavo (Angewandte Chemie-International Edition, 2024)
Oligo(phenyleneethynylene)s (OPEs) have attracted widespread attention due to their remarkable (opto)electronic and photophysical properties, which have enabled numerous applications. The versatile functionalization possibilities of OPEs make them unique candidates to form various shape-persistent geometries, including linear, triangular, rectangular, hexagonal and macrocyclic. However, as a result of this structural variety, it is oftentimes challenging to correlate molecular design with self-assembly properties. In this minireview, we have classified OPEs based on their molecular shapes and correlated them with their self-assembly behavior in solution. Particularly, we provide important insights into the aggregation propensity of the different molecular shapes and how to tune the association strength using various non-covalent interactions. Our classification will enable a better understanding of the structure-property correlation in OPEs, which is key to develop supramolecular functional materials.
Keywords: non-covalent interactions; Oligo(phenyleneethynylene)s; pi-conjugated systems; Self-assembly; Supramolecular Polymerizaton

Scalable approach using a gC3N4 -covalent organic framework hybrid catalyst towards sustainable hydrogen production from seawater and wastewater - Asokan, Kiran; Bhagyasree, T. M.; Devasia, George; Krishnamurty, Sailaja; Solim, Sabah; Rueda, Lina; Al-Mohannadi, Dhabia M.; Al-Hashimi, Mohammed; Kakosimos, Konstantinos; Santhosh Babu, Sukumaran (CHEMICAL SCIENCE, 2024)

Architecting nanographenes for efficient energy storage by tailoring molecular conformation and packing - Kumar, Viksit; Javaregowda, Bharathkumar H.; Devasia, George; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Santhosh Babu, Sukumaran (Journal of Materials Chemistry A, 2026)
Structural tuning of electrode materials to enhance electron transport, ion storage capacity, and Li+ diffusion is crucial for developing high-performance lithium-ion batteries (LIBs). In this context, organic functional materials are attractive candidates. Herein, we report a unique molecular design of regioisomeric nanographenes (NGs) with distinct geometries, packing, and topologies for lithium storage as LIB anodes. The nonplanar architectures suppress layer restacking compared to planar analogues, leading to improved electrochemical performance. The pi-extended helical NG 36NG, with larger interlayer spacing and a unique helical geometry, enables faster Li+ diffusion and delivers a higher specific capacity of 719.93 and 203.01 mAh g-1 at 0.1 and 1 A g-1, respectively, with stable performance over 6000 cycles, outperforming 27NG (525.46 and 113.17 mAh g-1 at 0.1 and 1 A g-1, respectively). Single-crystal X-ray analysis reveals markedly different molecular arrangements, directly correlating topology and packing with Li+ storage. This work highlights the critical role of molecular topology in LIB anodes and motivates the design of tailored pi-extended helical nanographenes for energy-storage applications.